Typical Pulmonary Carcinoid Presenting with Massive Hemoptysis in Early Pregnancy: A Case Report - Mohammadrasoul Sarmadi; Amirabbas Sheykhalo (Case Reports in Clinical Practice, 2026)
Massive hemoptysis during pregnancy is a rare but potentially life-threatening emergency, and pulmonary carcinoid is an unusual underlying cause. We report a 31-year-old primigravida who presented at five weeks of gestation with sudden massive hemoptysis. Chest computed tomography and flexible bronchoscopy revealed a hypervascular endobronchial lesion in the right bronchus intermedius causing partial airway obstruction and right middle lobe collapse. Histopathological and immunohistochemical examination confirmed a typical pulmonary carcinoid. Following multidisciplinary evaluation, definitive surgery was postponed until the second trimester because the patient remained clinically stable without recurrent bleeding. At 12 weeks of gestation, she underwent right middle lobectomy with systematic mediastinal lymph node dissection, achieving complete (R0) resection with negative lymph nodes. The postoperative course was uneventful, and both maternal recovery and fetal development remained favorable during follow-up. This case highlights the importance of multidisciplinary management and appropriately timed surgical intervention in achieving favorable maternal, fetal, and oncologic outcomesMassive hemoptysis during pregnancy is a rare but potentially life-threatening emergency, and pulmonary carcinoid is an unusual underlying cause. We report a 31-year-old primigravida who presented at five weeks of gestation with sudden massive hemoptysis. Chest computed tomography and flexible bronchoscopy revealed a hypervascular endobronchial lesion in the right bronchus intermedius causing partial airway obstruction and right middle lobe collapse. Histopathological and immunohistochemical examination confirmed a typical pulmonary carcinoid. Following multidisciplinary evaluation, definitive surgery was postponed until the second trimester because the patient remained clinically stable without recurrent bleeding. At 12 weeks of gestation, she underwent right middle lobectomy with systematic mediastinal lymph node dissection, achieving complete (R0) resection with negative lymph nodes. The postoperative course was uneventful, and both maternal recovery and fetal development remained favorable during follow-up. This case highlights the importance of multidisciplinary management and appropriately timed surgical intervention in achieving favorable maternal, fetal, and oncologic outcomes